On the lebesgue constants of fourier-laplace series by Riesz Means - Ahmad Fadly Nurullah, Rasedee; Rakhimov, Abdumalik A.; Ahmedov, Anvarjon A.; Torla, Hassan (IOP Publishing, 2017)
An asymptotic formula for the Lesbegue constant of the Riesz means of Fourier-Laplace series on the sphere obtained in this paper.